2018
DOI: 10.3233/jad-171061
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Subjective Cognitive Decline in Lesbian, Gay, Bisexual, and Transgender Older Adults

Abstract: Depression and functional impairment should be considered when screening LGBT older adults for cognitive impairment and dementia. Future research on the cognitive impairment and dementia risk in LGBT older adults is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 79 publications
3
53
0
Order By: Relevance
“…In the present study, Cronbach's alpha for the 8-item Cognition Function-Short Form was 0.90. SCD was assessed categorically via questions about memory complaints because an impaired memory is the most frequently reported complaint in research on SCD (e.g., [1,41,42]) and because previous cross-sectional research has utilised similar approaches to classifying SCD (e.g., [43,44]). Participants answered the following question: "Do you have memory complaints?".…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, Cronbach's alpha for the 8-item Cognition Function-Short Form was 0.90. SCD was assessed categorically via questions about memory complaints because an impaired memory is the most frequently reported complaint in research on SCD (e.g., [1,41,42]) and because previous cross-sectional research has utilised similar approaches to classifying SCD (e.g., [43,44]). Participants answered the following question: "Do you have memory complaints?".…”
Section: Methodsmentioning
confidence: 99%
“…The same study also found that under 1% of participants 80 and older reported a diagnosis of dementia, which was argued to potentially be related to selection and information bias. Another study found that about 25% of LGBT older adults reported subjective cognitive decline, which was particularly common among racial/ethnic minorities and those with depression and functional impairments . No study has compared MCI or dementia risk between sexual minorities and their heterosexual counterparts using the same protocol for diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding sexual orientation and risk of HAND, De Ronchi et al (2002) reported a higher odds ratio for the development on HIV-associated neurocognitive disorders in homosexual or bisexual subjects vs heterosexual subjects. Flatt et al (2018) found subjective cognitive decline in 25% of LGBT older adults; being a person of color, depressed, or reporting functional impairment were correlated with subjective cognitive decline.…”
Section: Introductionmentioning
confidence: 88%